An Extension of the Inverse Method to Probabilistic Timed Automata - André, Étienne; Sproston, Jeremy; Fribourg, Laurent (Electronic Communications of the EASST, 2009)
Probabilistic timed automata can be used to model systems in which probabilistic and timing behavior coexist. Verification of probabilistic timed automata models is generally performed with regard to a single reference valuation of the timing parameters. Given such a parameter valuation, we present a method for obtaining automatically a constraint on timing parameters for which the reachability probabilities (1) remain invariant and (2) are equal to the reachability probabilities for the reference valuation. The method relies on parametric analysis of a non-probabilistic version of the probabilistic timed automata model using the "inverse method’". Our approach is useful for avoiding repeated executions of probabilistic model checking analyses for the same model with different parameter valuations. We provide examples of the application of our technique to models of randomized protocols.